Diseño de una guía integral para la presentación de informes periciales contables y su aplicación en el sistema judicial ecuatoriano, del cantón Morona, período 2024. - Torres Guamán, Lisbeth Belén (2024)
This paper addresses the problem of the need for more standardization and quality in the presentation of expert accounting reports within the Ecuadorian justice system. The main objective of this research was to design a comprehensive guide for the presentation of standardized expert accounting reports and their practical application in the Ecuadorian judicial system in the province of Morona Santiago. The behavioral thread of the study was developed under a qualitative and quantitative approach, with descriptive, documentary, and field research, where the following methods were used: deductive, inductive, and hermeneutic; additionally, research techniques and instruments were applied, which facilitated the integral analysis of the object of study. The results obtained revealed that the expert accounting reports presented lacked a uniform structure, contained technical errors, inapplicability of the legal-accounting regulations, and did not follow a standardized format specialized in accounting; in addition to this, the lack of continuous training and updating of knowledge for the accounting experts was identified. Therefore, there is an imminent need to implement a comprehensive guide to facilitate the work of the experts, ensuring that the reports comply with the legal and technical standards necessary for their proper application and interpretation by the justice administrators within the legal system.